2016
DOI: 10.18632/oncotarget.12861
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-101 reverses temozolomide resistance by inhibition of GSK3β in glioblastoma

Abstract: Glioblastoma multiforme (GBM) is a chemotherapy-resistant brain tumor with limited treatment options. Temozolomide (TMZ), an alkylating agent, is a front-line chemotherapeutic drug currently employed in GBM. Although it is currently the most promising chemotherapy for GBM, resistance to TMZ is also common and accounts for many treatment failures. Therefore, understanding the underlying mechanisms that generate resistance is essential to develop more effective chemotherapies. Here, we show that microRNA-101 (mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…Previously, it was reported that miR‐101 sensitized resistant GBM cells to TMZ through downregulation of GSK3 β , which is a multifunctional protein kinase that regulates various cellular pathways . Moreover, inhibition of GSK3 β could enhance TMZ effect by decreasing O 6 ‐methylguanine‐DNA methyltransferase (MGMT) expression via promoter methylation .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it was reported that miR‐101 sensitized resistant GBM cells to TMZ through downregulation of GSK3 β , which is a multifunctional protein kinase that regulates various cellular pathways . Moreover, inhibition of GSK3 β could enhance TMZ effect by decreasing O 6 ‐methylguanine‐DNA methyltransferase (MGMT) expression via promoter methylation .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Tian et al. indicated that miR‐101 reversed TMZ resistance by inhibition of GSK3 β in GBM. Moreover, the suppression of GSK3 β could subsequently be decreasing MGMT expression via promoter methylation to regulate the TMZ resistance in GBM .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that miR-101 plays key roles in BC progression. Although miR-101 has been reported to target many downstream genes, including CDK8 [10], c-FOS [11], CXCR7 [18], SOX9 [14, 19] and GSK3β [20], the potential correlation between miR-101 and Sex-determining region Y-box 2 (SOX2) in BC is still unknown and needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…GSK3β is also a target of miR-101b (Tian et al 2016). Treatment of thapsigargin stimulated fibroblasts with miR-101b mimic results in decreased abundance of GSK3β mRNA (Fig.…”
Section: Thapsigargin Dependent Up-regulation Of Mir-101b and Effect mentioning
confidence: 92%